Learning and teaching mathematics using simulations : plus 2000 examples from physics - Röss, Dieter, 1932- (De Gruyter textbook., 2011)
This is a unique, comprehensive and documented collection of simulations in mathematics and physics: More than 2000 simulations, offered on our webpage for comfortable use online. The book, written by an experienced teacher and practitioner, contains a complete introduction to mathematics and the documentation to the simulations. This is a great way to learn mathematics and physics. Suitable for courses in Mathematics for Engineering and Sciences.